Faktor-Faktor yang Mempengaruhi Kinerja Auditor - Khayatun Nufus; Pascal Fadillah (Department of Accounting-Faculty of Economic and Business (FEB), 2022)
The purpose of this research is to analyze the influence of auditing structures, role conflicts, role ambiguity, reward systems, the effectiveness of the use of accounting information system technology on auditors’ performance. This study used primary data by distributing questionnaires to auditors who worked for the public accounting firms in Tangerang Raya. Determination of the sample using simple random sampling method. This study used a sample of 77 respondents. Data were analyze using multiple linear regression analysis methods with the help of SPSS 20 programme. The results of this research indicate that audit structure and effectiveness of the use of accounting information system technology has a impact on auditor performance. Meanwhile, role conflict, role ambiguity and reward system does not have impact on auditor performance.